Transcriptomic Landscape of Medicinal Dendrobium Reveals Genes Associated With the Biosynthesis of Bioactive Components - Wang, Zhicai; Zhao, Meili; Cui, Hongqiu; Li, Jian; Wang, Meina (Frontiers in Plant Science, 2020)
Many plants of Dendrobium genus are precious traditional herbs with high commercial value and excellent medicinal effects. They are perennial aerophytes or epiphytes of terrestrial orchids growing on cliffs, tree trunks covered with mosses in forests throughout the tropical and subtropical Asia and eastern Australia. The stem contains a variety of bioactive components, including polysaccharides and alkaloids, with strong antioxidant, neuroprotective and immunomodulatory effects. Great attention has been drawn to the Dendrobium genus regarding its medicinal effectiveness, and the related researches have been accumulating rapidly in recent years. The bioactive components are mainly the intermediates or final products produced in secondary metabolite biosynthesis. Thus far, the activity, molecular structure and composition of major medicinal ingredients have been partially elucidated, and the sequencing of several transcriptomes are starting to shed new lights on the biosynthesis regulation mechanism. This paper reviewed the advances of researches concerning the biosynthetic pathways of medicinal secondary metabolites from Dendrobium, especially the large number of related genes, with the hope of further promoting the development and utilization of those components, and correspondingly protecting the Dendrobium resources in more effective ways.